Shaping Farmer Regeneration in Early Childhood Through Verticulture Farming System Education - Sulik Sofinda; Sugeng Santoso; Setyo Ajie Wibowo; Yayang Ristiana Putri (Journal of Early Childhood Education Research, 2025)
Purpose: Indonesia is currently facing a critical challenge characterized by the declining interest of younger generations in the agricultural sector, as evidenced by the aging farmer phenomenon. This demographic shift poses a significant threat to the sustainability of national food production and agricultural development. To address this pressing issue, this study aims to introduce verticulture farming systems to kindergarten students as an early educational intervention designed to foster agricultural awareness and cultivate future farmer regeneration among young children. Methodology: This study employed a descriptive qualitative approach conducted at Dharma Wanita Maliran 2 Kindergarten in Blitar Regency, East Java, Indonesia. The participants consisted of Group B students aged five to six years. Data were collected through multiple techniques, including systematic observation of children's engagement during agricultural activities, semi-structured interviews with teachers and students, direct hands-on training sessions, and a comprehensive literature review. The educational activities encompassed the introduction of verticulture farming concepts, practical planting experiences, and ongoing plant maintenance routines, further reinforced through the proposed "Friday Gardening" program as a sustainable school-based initiative. Results: The findings revealed that children demonstrated high levels of enthusiasm and active participation throughout the verticulture educational activities. Students gained a meaningful understanding of the benefits of farming and showed improved knowledge regarding plant growth processes. Beyond the acquisition of technical agricultural skills, the activities effectively instilled essential developmental values, including a sense of responsibility, heightened environmental awareness, teamwork, and collaborative behavior among the young learners. Conclusions: This study concludes that verticulture-based farming education can serve as an effective and contextually relevant strategy to initiate farmer regeneration from an early age. Integrating agricultural education into early childhood curricula has the potential to shape positive attitudes toward farming and contribute to addressing the generational gap in Indonesia's agricultural workforce.